Strategi pembangunan instalasi pengolahan air limbah komunal berbasis partisipasi masyarakat - Adnyana, I Gede; Sumantra, I.K (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The concept of community-based wastewater management is considered as a concept that is in line with the domestic wastewater treatment program. Therefore, through a community-based total sanitation program by constructing communal wastewater treatment plants (WWTP) using a community based participatory research pattern, it is hoped that the handling of sanitation problems in Bajera Village can be optimized. The objective to be achieved in this research is to formulate a participatory Communal WWTP development strategy in accordance with the level of community needs in Bajera Village. Methods: The design of this study used a qualitative method involving seven field participants and five validation participants. Data collection techniques using open questionnaires, semi-structured interviews and FGD. Validity and reliability is done through triangulation of sources, methods, and data. The collected data is then analyzed using the interpretative phenomenological analysis (IPA) method. Results: Based on the research carried out, there is still a lot of community wastewater discharged directly into the environment without going through treatment first. This certainly will greatly affect the cleanliness and health of the environment. To overcome these problems, it is necessary to build a wastewater treatment plant by involving the surrounding community by implementing strategies in accordance with the social conditions of the community. Conclusion: The formulated strategy, namely: Conducting education through counseling by involving relevant regional officials. Involving traditional leaders, religious leaders, youth leaders, women leaders and migrant communities starting from the planning, development, management and monitoring stages. Make awig-awig and village regulations on waste water management that are used as the basis for regularity in community life.